Inovasi Nanoagroteknologi untuk Pertanian Berkelanjutan: Mengintegrasikan Smart Technology dengan Praktik Ramah Lingkungan - Hasibuan, Molani Paulina; Agustina Nst, Mutiara; Panda, Florentina Maria; Agustini, Dwi (Alpatih Harapan Semesta, 2024)
Global climate change and rapid population growth have created significant challenges to food security. To overcome these challenges, innovative technologies are needed that are capable of increasing agricultural yields in a sustainable manner. This research aims to explore the concept of Nanoagrotechnology as a smart technology that has the potential to increase agricultural productivity and efficiency while maintaining environmental sustainability. Nanoagrotechnology integrates nanotechnology applications in crop production and protection, such as the use of nano-fertilisers, nanopesticides, nanobiosensors, and nano-based technologies for remediation of contaminated soil. This research method uses a literature review approach by analysing various study results related to the application of nanotechnology in the agricultural sector. The results of the analysis show that nanotechnology is able to increase the efficiency of resource use, reduce negative environmental impacts, and produce crops with better quality and quantity. Nanoagrotechnology is thus a potential solution to the challenges of modern agriculture and contributes to global food security.